ОЦІНКА ОБМІННОЇ ПОТУЖНОСТІ В ТРИФАЗНИХ ЛОКАЛЬНИХ СИСТЕМАХ ЕЛЕКТРОПОСТАЧАННЯ З ВРАХУВАННЯМ НОРМОВАНИХ ПОКАЗНИКІВ ЯКОСТІ ЕЛЕКТРОЕНЕРГІЇ - Денисюк, С.П.; Горенко, Д.С. (Інститут електродинаміки Національної академії наук України, 2018)
The analysis of the mutual influence of elements in the intersection of three-phase tri-conductor and four-conductor Local Electrical Supply Systems (LESS) is carried out. The analysis of the current normative documents that normalize the electromagnetic compatibility of electrotechnical facilities and systems both in Ukraine and abroad is carried out. It is suggested to use the share of mutual influence of phase elements to evaluate the exchange processes in the intersection of three-phase LESS. The sequence of determination of the share of mutual influence in the intersection of three-phase LESS triple-conductor and four-conductor execution is presented. The graphic dependences of the change in the proportion of mutual influence and the coefficients of asymmetry at different levels of asymmetry for three conductive and four-conductor three-phase LESS are constructed. The analytical expressions of the connection of the asymmetry coefficients in reciprocal and zero sequences are given from the share of mutual influence in the intersection of the three-phase LESS. The possibility of the normalization of the share of mutual influence, as an additional indicator of exchange processes in three-phase LESS, is argued.  References 17, figures 3, table.